What's on offer: how do parties appeal to women voters in election manifestos?. Issue 4 (2nd October 2021) - Sanders, Anna; Gains, Francesca; Annesley, Claire
ABSTRACT: Existing research has tended to examine party manifesto appeals to women voters as a homogenous group however we know relatively little about how parties appeal to different groups of women voters. Yet there are strong incentives for parties to respond to and reflect diversity in women's voting behaviour. Through a gendered analysis of party manifestos at the 2015, 2017 and 2019 British general elections, we investigate the spread and reach of parties' policy appeals to women voters. We find that, while the principal state-wide parties are increasingly recognizing women's diversity in their policy pledges, some groups of women remain marginalized from parties' electoral agendas. Our findings extend the empirical and analytical understanding of how political parties make gendered appeals during election times and to whom. We argue the way parties seek to appeal to the diversity of women is important for the analysis of both issue ownership and interparty competition for women's votes. Additionally, we make a normative case for parties to recognize diversity and intersectionality in their manifesto policy promises.